Application of Blockchain and Artificial Intelligence Technology in Large Forestry Enterprise Archives Management - Deng xiaofei, Zhang yuanyuan (Forest Chemicals Review)
The archives management information system of large forestry enterprises is an important part of the construction of "digital forestry" in China. As the underlying technology foundation of the next generation of trust Internet, the importance and extensibility of blockchain cannot be ignored. As an emerging technology and tool, it will also have an important impact on the development of library, information and archives discipline. This paper studies the application of blockchain in large enterprise archives management. This paper constructs the archives intelligent service system of "artificial intelligence + blockchain" from four dimensions of infrastructure layer, archives resource layer, technology processing layer and service application layer. At the same time, this paper deeply excavates the practical application examples of "AI + blockchain archives" at home and abroad, and discusses how AI can enable archives intelligent service. Finally, the archives intelligent service system of "artificial intelligence + blockchain" was initially constructed. The results show that the service system can improve the efficiency and accuracy of archives management in large enterprises.